Design of a wireless scoring system for fencing using RFID technology - Alvarez, J. A.; Cristobal, M. V.; Gamalinda, M. T.; Malino, A.; Miguel, J. (International Journal of Sports Science and Engineering, 2008)
This paper focuses on the implementation of a wireless scoring system using RFID technology. It also contains the objectives and significance of carrying out the study. Existing electronic and wireless scoring system are presented to develop comparison with our own scoring system. Discussion on how the prototype functions are also included in this paper. The functionality and performance of the final prototype were shown through results obtained after testing. Conclusions and future directives are stated at the latter part of the paper.